The Socio-demographic Factors Influence on Anti-Social Behaviour among Children (Case Study of Bobaracho Area, Nyaribari Chache, Kisii Kenya) - Anika, Alice A.; Michael, Omwenga; Lambert, Edward (European Journal of Applied Sciences, 2024)
This study investigates the influence of social demographic characteristics on antisocial behaviours among children in the Bobaracho area of NyaribariChache constituency, Kisii County, Kenya. Antisocial behaviour, characterized by actions that violate societal norms and harm others, poses significant challenges to community cohesion and child development. The research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to gather comprehensive data from a sample of 150 children aged 6-12 years and their guardians. Key demographic factors examined include age, gender, family structure, parental education, and socioeconomic status. The findings reveal a significant correlation between low parental education and increased antisocial behaviours, particularly among boys. Additionally, children from single-parent households exhibited higher levels of aggression and defiance compared to those from two-parent families. Qualitative insights highlight the role of peer influence and community environment in shaping children's behaviour. The study underscores the importance of addressing social demographic factors in interventions aimed at reducing antisocial behaviours. Recommendations include community-based programs that promote parental engagement and education, as well as initiatives to foster positive peer relationships. This research contributes to the understanding of how social demographics intersect with child behaviour, providing a foundation for policymakers and educators to develop targeted strategies for promoting positive social development among children in Kisii County.